The Super-vision of Autoethnographic Dissertation Studies: Transformative Stories of the Supervisor and the Supervised Revealed. Issue 2 (May 2022) - Tisdell, Elizabeth J.; Whalen, Gina C.; Johnson, Mira
The purpose of this paper is to explore the super-vision of dissertations, from the perspective of the supervisor and two supervisees who did dissertations that had an evocative autoethnographic component. We argue that autoethnography in context of scholarly writing encourages both an inner looking, and an outward looking that results in a super-vision, that is the result of the relationship between the supervisor and the supervisee, which evokes further insights, analysis, and reflexive stories.